Zanesljivost in smiselnost opazovanja psiholoških dimenzij trenerjev v športu mladih - Železnik Mežan, Lea (Šport (Ljubljana), 2024)
Personality is a network of more or less complex characteristics. There are general and individual characteristics. Many studies have already posed the question of the most important personality traits of successful coaches. Many of them have investigated the behaviour of coaches. However, an instrument for observing the behaviour of coaches does not yet exist in Slovenia. The aim of our study was to create an observation list to assess the behaviour of coaches working with youth athletes. The list was validated for reliability. Two raters rated six coaches in 12 areas of observation. The data were statistically analysed using IBM SPSS. Interobserver reliability was calculated using interclass correlation coefficients. They showed an excellent agreement of the average values for all coaches. On the other hand, scores were not reliable in all areas of observation. Observing the behaviour of coaches seems to be useful as it can provide information about unconscious actions. However, it is very difficult to create such an observation list and the observation of psychological dimensions is complex and time-consuming. Our list needs some corrections and we would recommend that the assessors are better trained next time. Nevertheless, the list represents an important contribution to kinesiological science and is also useful for other sporting contexts.
Keywords: coach; observation; opazovanje; psihološke dimenzije; psychological dimensions; šport; šport mladih; trener; youth sport